2014
DOI: 10.1111/den.12217
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of technical aspects and complications of endoscopic submucosal dissection for large superficial colorectal tumors

Abstract: Procedure speed for Group B was faster than that for Group A. Group B was treated as safely as Group A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Although large lesions are associated with a longer procedure time, size did not affect the complete resection rate and speed. Furthermore, in one study, the larger diameter of a lesion was associated with a greater procedure speed [30,31].…”
Section: Discussionmentioning
confidence: 97%
“…Although large lesions are associated with a longer procedure time, size did not affect the complete resection rate and speed. Furthermore, in one study, the larger diameter of a lesion was associated with a greater procedure speed [30,31].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated that poor submucosal lifting, presence of fibrosis, and paradoxical movement of the endoscope are associated with difficult ESD and increased risk of perforation . The scissor‐type knife can be handled easily like a biopsy forceps even in an unstable position, because the operator simply grasps the target tissue and cuts it without endoscopic movements, even at a remote distance, and a scissor‐type knife might reduce the risk of perforation . This enables the operator to overcome difficult situations, such as an unstable approach to the lesion, and inability to access the submucosal layer for dissection.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] Development of ESD in Eastern countries has enabled the en bloc resection of large superficial colorectal tumors regardless of their size and location. [29][30][31] The Japan Gastroenterological Endoscopy Society stated the indications for ESD of colorectal tumors as follows: (i) lesions for which en bloc resection with snare EMR is difficult to apply; (ii) mucosal tumors with submucosal fibrosis; (iii) sporadic localized tumors in conditions of chronic inflammation such as ulcerative colitis; and (iv) local residual or recurrent early carcinomas after endoscopic resection. 11 ESD is usually used for colorectal tumors >20 mm for which en bloc resection with snare EMR is difficult to carry out.…”
Section: Piecemeal Emr Versus En Bloc Esdmentioning
confidence: 99%
“…However, the safety and feasibility of ESD for tumors >50 mm have been reported in Japan. 12,29,31 Recently, the feasibility of ESD for the treatment of large tumors >10 cm was reported from Korea. 32 Although the article reported a long procedure time (average 270 min) and high perforation rate (22%), a high en bloc R0 resection rate (89%) was documented.…”
Section: Piecemeal Emr Versus En Bloc Esdmentioning
confidence: 99%
See 1 more Smart Citation